Analysis of Budget Planning, Project Completion Time, and Infrastructure Quality on Budget Efficiency and Effectiveness - Khuluq, Muhammad Husnul; Rahmawati, Imelda Dian (Amkop Management Accounting Review (AMAR), 2025)
The budget is an integral part of a financial plan that reflects institutional policy decisions over a specific period. As an economic policy instrument, the budget plays a crucial role in income distribution and in promoting economic growth and stability. Within the framework of regional autonomy, budget management is carried out independently by local governments to prevent the concentration of power in the central government. This decentralization is expected to encourage more effective, efficient, and transparent public service delivery. This study was motivated by a research gap in the implementation of infrastructure projects, where the planning and document preparation processes are often carried out simultaneously with the physical implementation of the project. This has the potential to cause budget inefficiency and reduce the effectiveness of project achievement. This study aims to analyze the influence of Budget Planning, Project Completion Time, and Infrastructure Quality on Budget Efficiency and Effectiveness in infrastructure projects managed by the Public Works, Highways, and Water Resources Agency of Sidoarjo Regency. This study employs a quantitative approach, utilizing Partial Least Squares Structural Equation Modeling (PLS-SEM) analysis via SmartPLS software. The sample consists of 100 respondents selected using total sampling, as the entire relevant population was included as respondents.